Finance and governance of capital cities in federal systems - Slack, Enid, 1951-; Chattopadhyay, Rupak (Thematic issues in federalism, 2009)
Examines federal policies towards capital cities, with an emphasis on how capital cities are funded and governed, and the extent to which the federal government compensates them for their unique role.